Pemeliharaan Mesin Es Batu Kristal untuk Meningkatkan Keberlanjutan Usaha Mikro - Effendi, Ryan; Ernayani, Rihfenti (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Crystal ice micro-enterprises play a significant role in meeting the needs of households, the culinary industry, and the service sector in urban areas. However, limited knowledge among business owners regarding the care and maintenance of production machinery often leads to equipment damage, increased operational costs, and a decline in business sustainability. This community service activity aims to enhance the knowledge and skills of crystal ice micro-entrepreneurs in Sepinggan Subdistrict, Balikpapan City, through training on the maintenance and upkeep of production machines. The implementation methods include counseling sessions, hands-on practical training, and interactive discussions. The results indicate an improvement in participants’ understanding of preventive machine maintenance, equipment cleanliness and sanitation, as well as their ability to independently perform basic maintenance tasks. Therefore, this activity contributes to improving production efficiency and supporting the sustainability of micro enterprises.